2010
DOI: 10.1149/1.3476288
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of Germanium Nanowires from Hexamethyldigermane: Influence of the Substrate Pretreatment

Abstract: Germanium nanowires ͑GeNWs͒ were synthesized by low pressure chemical vapor deposition of hexamethyldigermane ͑GeMe 3 ͒ 2 at 490°C and a pressure of 90-100 Pa. GeNWs of several nanometers in diameter and a few micrometers in length were deposited onto substrates made of stainless steel, Fe, Mo, Ta, W, Si, and SiO 2 . The influence of surface pretreatment of the substrates ͑roughening of surface, grooves made by a diamond tip or Ge thermal evaporation͒ is discussed. GeNW deposits were studied using scanning ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 22 publications
1
6
1
Order By: Relevance
“…Mathur et al [225] also explored the growth mechanism of Ge nanowires grown on Fe substrates. No evidence of spherical seeds was found at the tips of the nanowires, unlike those reported by Dřínek et al [141] for Ge nanowire growth with same Fe substrates. Recently, Dřínek et al [142] also reported the formation of core-shell Ge-Si/C nanowires in the absence of external catalytic seeds.…”
Section: Growth Mechanisms Of Self-seeded Growth By Vapour-phase Methodscontrasting
confidence: 70%
See 3 more Smart Citations
“…Mathur et al [225] also explored the growth mechanism of Ge nanowires grown on Fe substrates. No evidence of spherical seeds was found at the tips of the nanowires, unlike those reported by Dřínek et al [141] for Ge nanowire growth with same Fe substrates. Recently, Dřínek et al [142] also reported the formation of core-shell Ge-Si/C nanowires in the absence of external catalytic seeds.…”
Section: Growth Mechanisms Of Self-seeded Growth By Vapour-phase Methodscontrasting
confidence: 70%
“…Substrates only accommodate catalytic droplets (Ge nanoparticles in this case) for further nanowire growth. Dřínek et al [141] screened a series of substrates such as stainless steel, Fe, Mo, Ta, W and SiO 2 at a reaction temperature of 490 • C, with (GeMe 3 ) 2 as the Ge precursor, to evaluate the role of the substrates in self-seeded Ge nanowire growth. Even though Fe, Mo and Ta form intermetallic phases with Ge, only Fe does it at the reaction temperature of 490 • C, while the others form at temperatures of~700 and 600 • C, respectively [224].…”
Section: Growth Mechanisms Of Self-seeded Growth By Vapour-phase Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequently, the Ge thin films were deposited onto the steel substrates. The deposition procedure has been described elsewhere (Drinek et al, 2010;Krabac et al, 2012); nevertheless, the discussed deposition process was carried out at 650°C for 90 minutes and under the pressure of 40-80 Pa during the deposition process. Moreover, hexamethyldigermane (technical grade, Sigma-Aldrich Corporation, USA) was used as a volatile precursor.…”
Section: Methodsmentioning
confidence: 99%